2016
DOI: 10.1021/acs.jpcb.6b02923
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Dimer and Trimer Formation of Tri-n-butyl Phosphates in Different Alkane Diluents: FTIR Study

Abstract: Tri-n-butyl phosphate (TBP), a representative of neutral organophosphorous metal-ion-extracting reagents, is an important ligand used in solvent extraction processes for the recovery of uranium and plutonium from spent nuclear fuel, as well as other non-nuclear applications. Ligand-ligand and organic solvent-ligand interactions play an important role in these processes. The self-association behavior of TBP in various alkane diluents of different chain lengths (8, 12, and 16 carbons) and a branched alkane (iso-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 33 publications
(95 reference statements)
5
13
0
Order By: Relevance
“…Our simulated TBP self-association values of k 2 = 1.54 ± 0.07 M −1 and k 3 = 0.56 ± 0.09 M −1 showed excellent agreement with our experimental study reported in a separate study. 21 The results from this work validate the accuracy of our optimized force fields for TBP and n-dodecane molecules. The new insights into the conformational behaviors of the TBP molecule as a monomer and as part of an aggregate will greatly aid in the understanding of the complex formation between TBP and metal ions and the third phase formation later on when we pursue our ambitious goal of simulating a complete solvent extraction system.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Our simulated TBP self-association values of k 2 = 1.54 ± 0.07 M −1 and k 3 = 0.56 ± 0.09 M −1 showed excellent agreement with our experimental study reported in a separate study. 21 The results from this work validate the accuracy of our optimized force fields for TBP and n-dodecane molecules. The new insights into the conformational behaviors of the TBP molecule as a monomer and as part of an aggregate will greatly aid in the understanding of the complex formation between TBP and metal ions and the third phase formation later on when we pursue our ambitious goal of simulating a complete solvent extraction system.…”
Section: Discussionsupporting
confidence: 71%
“…We have also carried out an experimental study employing the FTIR technique in parallel with this MD work to validate our results. 21 The agreement between these studies will be discussed throughout this section.…”
Section: Radial Distribution Functions At Different Tbp Concentrationsmentioning
confidence: 70%
See 3 more Smart Citations